Prevalence of venous thromboembolism at pretreatment screening and associated risk factors in 2086 patients with gynecological cancer. Issue 5 (8th March 2020) - Tasaka, Nobutaka; Minaguchi, Takeo; Hosokawa, Yoshihiko; Takao, Wataru; Itagaki, Hiroya; Nishida, Keiko; Akiyama, Azusa; Shikama, Ayumi; Ochi, Hiroyuki; Satoh, Toyomi
Abstract: Aim: Postoperative pulmonary embolism can be a fatal surgical complication and is thought to occur secondary to asymptomatic venous thromboembolism (VTE) that exists preoperatively in some patients. The purpose of this study was to clarify the frequency and risk factors of pretreatment VTE in gynecological cancer patients. Methods: This study investigated 2086 patients with gynecological cancer (cervix, n = 754; endometrium, n = 862; ovary, n = 470) who underwent initial treatment between 2004 and 2017. Pretreatment VTE screening was performed with D‐dimer (DD) levels in these patients. Based on this, the associated risk factors were retrospectively analyzed. Results: Pretreatment VTE was discovered in 7.3% of patients with cervical cancer, 11.5% of those with endometrial cancer and 27.0% of those with ovarian cancer. Significant independent risk factors were: age greater than or equal to 60 years and tumor long diameter greater than or equal to 40 mm for cervical cancer; age greater than or equal to 60 years, stage III/IV advanced disease, clear cell carcinoma and tumor long diameter greater than or equal to 60 mm for endometrial cancer; and age greater than or equal to 60 years, clear cell carcinoma and massive ascites for ovarian cancer. Conclusion: Pretreatment asymptomatic VTE is very frequent in gynecological cancer patients. It may be beneficial to consider measuring DD or performing venous ultrasonography in patients with the above risk factors.